Occupational Stressors of Prison Staff: An Integrative Review - Sabrina Azevedo Wagner Benetti; Eliane Raquel Rieth Benetti; Cíntia Beatriz Goi; Mauren Pimentel Lima; Taís Carpes Lanes; Adriane Cristina Bernat Kolankiewicz; Marcos Benetti; Rafaela Andolhe (Psico-USF)
Abstract The objective of this integrative review was to analyze and synthesize the scientific literature on occupational stressors among workers in prison institutions. Searches were conducted in the PSYCinfo, CINAHL, EMBASE, SCOPUS, Web of Science, and MEDLINE/PubMed databases without any time restrictions. Out of 1,067 articles, 28 met the eligibility criteria. Most studies employed a quantitative approach and were published in English. Factors related to safety-such as physical danger, violence, aggression, threats, and inherent dangers of working in this environment-were highlighted as occupational stressors in prison institutions. Additionally, role conflict and ambiguity, low job control, and work-family conflicts were identified as contributing to high stress levels, negatively impacting both individuals and organizations. The limitations of the study include that the selected articles had level 6 evidence rating and did not differentiate between occupational stressors in each job role.